THE ROLE OF INDONESIAN WAQF BOARD IN PROMOTING AND DEVELOPING WAQF IN INDONESIA - Uswatun Hasanah (Universitas Trisakti, 2014)
Indonesia is a country that has quite a lot of waqf lands, amounting to 3.492.045.373m2, distributed in 420 003 locations. Unfortunately the waqf lands are not managed productively, so that they cannot be utilized to improve the public welfare. To promote and develop waqf in Indonesia, in the Law No. 41 year 2004 it is mandated to set up Indonesian Waqf Board. In 2007 President of the Republic of Indonesia, Dr. Susilo Bambang Yudhoyono signed a decree on the formation of Indonesian Waqf Board (BWI). Now BWI has reached it seventh year of age. The question arising is, how is the role of BWI in promoting and developing waqf in Indonesia? Despite very limited funds, BWI with its six divisions has been running its programs, and even to develop waqf in Indonesia, presently BWI has already established 24 representatives, and 9 representatives are still in the process. Hopefully with representatives in every province, Indonesian waqf can evolve in a productive manner so that the results can be used to improve the welfare of the people. Keywords: waqf, productive, and wellfare.